2020
DOI: 10.1101/2020.05.08.084475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local genetic correlation analysis reveals heterogeneous etiologic sharing of complex traits

Abstract: Local genetic correlation quantifies the genetic similarity of complex traits in specific genomic regions, which could shed unique light on etiologic sharing and provide additional mechanistic insights into the genetic basis of complex traits compared to global genetic correlation. However, accurate estimation of local genetic correlation remains challenging, in part due to extensive linkage disequilibrium in local genomic regions and pervasive sample overlap across studies. We introduce SUPERGNOVA, a unified … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 110 publications
0
33
0
Order By: Relevance
“…Followed up in three independent cohorts of ASD proband-parent trios, we identified significant over-transmission of the direct component of EA from healthy parents to ASD probands but not to the healthy siblings. These results added value to the recent advances in understanding common genetic variations' roles in ASD etiology 33,35,38,39 and provided critical new insights into the shared genetic basis of ASD and cognitive ability. These results also call for extreme caution in human genome editing and embryo screening 40 .…”
Section: Discussionmentioning
confidence: 82%
“…Followed up in three independent cohorts of ASD proband-parent trios, we identified significant over-transmission of the direct component of EA from healthy parents to ASD probands but not to the healthy siblings. These results added value to the recent advances in understanding common genetic variations' roles in ASD etiology 33,35,38,39 and provided critical new insights into the shared genetic basis of ASD and cognitive ability. These results also call for extreme caution in human genome editing and embryo screening 40 .…”
Section: Discussionmentioning
confidence: 82%
“…Genetic correlation estimation methods can be classified as methods requiring individual-level data 6,[10][11][12][13] and methods that use GWAS summary statistics as input [3][4][5][14][15][16][17][18][19] . Restricted maximum likelihood (REML) is the most common approach among individual-level-data-based methods where genetic correlation is estimated as one of the (co)variance component parameters of LMM.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-trait linkage disequilibrium (LD) score regression (LDSC) is the first method that uses GWAS summary statistics alone as input to estimate genetic correlation 3 . Built upon LDSC, methods have been developed to estimate annotation-stratified 4 , local [14][15][16] , and trans-ethnic 17 genetic correlation from GWAS summary statistics. Zhang et al 15 showed that most existing methods are based on the idea of minimizing the "distance" between the empirical and theoretical covariance matrices of marginal z-scores obtained from GWASs of two phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, heritability studies and GWAS implicated critical roles of common SNPs in the etiology of ASD [5, 6]. Additionally, multi-trait modeling revealed strong genetic correlations of ASD with various complex traits [7]. Compared to other approaches, pTDT leverages a robust, family-based design to assess the transmission disequilibrium of complex traits’ polygenic risk between healthy parents and ASD probands and shed important light on the shared genetics between ASD and other genetically correlated phenotypes [3].…”
Section: Introductionmentioning
confidence: 99%